Faith as Evidential Venture: A Comparison of John Bishop and John Schellenberg's Views on Faith - Karim Karami; Seyed Amir Akrami (پژوهشنامه فلسفه دین, 2023)
One of the significant issues in religious epistemology is how to describe and justify faith. In religious epistemology, various descriptive and justifying models of faith have been proposed, one of which is faith as an “evidential venture.” In this view, one who is aware of the absence of sufficient reasons, in respect of evidential ambiguity, can Venture in favor of religious belief or faith. This article introduces two descriptive models of faith from the viewpoint of John Bishop and John Schellenberg –two significant proponents of faith as an evidential venture. The next step discusses how they evaluate their faith models in terms of four criteria: evidential, psychological, moral, and practical. John Bishop presents his faith model as a fully-doxastic venture, and John Schellenberg as a nondoxastic venture. Finally, by comparing these two models, some features that should be considered in proposing descriptive and justifying models of faith are mentioned: paying attention to diachronic justification besides the synchronic one, paying attention to the epistemic sensitivity of the believers based on an outsider concern about religion, and considering the personal and psychological distinctions among each person of believers and nonbelievers.